RELEVANSI PEMBAHARUAN ISLAM BIDANG HUKUM KELUARGA TERHADAP EGALITER LAKI-LAKI DAN PEREMPUAN - Arif Sugitanata (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2020)
In the kinship system in the Arab era, ignorance of their wives was nothing more like merchandise, which could also be inherited. When their husbands die, these wives will belong to the sons who are left behind and some will also marry them and marry them to whomever they like. These incidents leave women to a very low and despicable level. Thus the ignorance community is committed to harassing women, humiliating and depriving them of their rights in a very long historical period. The era of ignorance is like a dark spot in women's civilization. Islam is present as a religion of renewal that is blessed by God Almighty through the intermediary of the Prophet Muhammad SAW, who is present as a bearer of guidance to the truth from Allah SWT, which is preached by His Messenger, as a result of the deviations that have been committed by his followers. Therefore, Islam is a religion that is true and blessed by Allah SWT until the end of time. Then the presence of Islam provides space for justice for women and elevates their position and gives equal roles to men, both for their rights, dignity and their involvement with men in various fields, except in fields that are not in accordance with their nature and nature. as a woman.